Criminal Liability in the Misuse of Donations by the Aksi Cepat Tanggap Foundation: A Juridical Analysis of Justifying and Excusing Grounds - Nuraeni, Dewi Sintia; Juhana, Ujuh (Journal of Law, Politic and Humanities, 2025)
The case of misuse of donations by the Aksi Cepat Tanggap Foundation (ACT) in the management of funds from Boeing for the heirs of the victims of the Lion Air JT-610 accident has become an important issue in criminal law enforcement in Indonesia. This study aims to analyze the application of criminal sanctions against the misuse of social funds by foundation administrators who are charged with embezzlement in office as stipulated in Article 374 of the Criminal Code jo Article 55 of the Criminal Code. This research uses a normative juridical approach and an empirical juridical approach with a case study of the South Jakarta District Court's decision Number 865/Pid.B/2022. The results of the study show that the elements of embezzlement are legally and convincingly proven. The defendant was sentenced to 3 years in prison for being proven to have misused social funds for purposes that were not in accordance with the designation. The study also highlights the absence of a pardon or justification that can absolve the defendant from criminal liability. This decision is an important reflection for strengthening regulations, transparency of philanthropic institutions, and fair law enforcement in the management of social funds.